The effect of fiber orientation on fracture response of metallic fiber-reinforced adhesive thin films. Issue 1 (January 2018) - Razavi, S.M.J.; Sandnes, L.; Torgersen, J.; Berto, F.
HIGHLIGHTS: The metal fibers were incorporated with different orientations in the adhesive layer of a bonded joint. Fracture tests were conducted on double cantilever beam (DCB) specimens to study the fracture behavior of metallic fiber-reinforced adhesives. The orientation of the fibers and the distance between the fibers were the key parameter in bond design. Longitudinally reinforced adhesives resulted in higher fracture energy improvements compared to the laterally reinforced adhesives. Reducing the distance between the fibers, considerably increased the fracture energy of epoxy adhesive. ABSTRACT: Incorporation of metallic fibers into the adhesive layer can significantly improve the mechanical behavior of the adhesive joint. This paper aims to assess the fracture behavior of an epoxy adhesive reinforced by longitudinal and lateral metallic fibers. Double cantilever beam (DCB) specimens were used to obtain the fracture energy of both non-reinforced and reinforced adhesives under mode I loading condition. In addition to the fiber orientation, the distance between the metal fibers was considered as the second key parameter in the experiments. It was concluded that although incorporation of metallic fibers in the adhesive layer improves the fracture behavior of neat adhesive, however, higher improvements were observed for the adhesive reinforced with longitudinal fibers. Furthermore, reducing the fiber distances resulted in higher values of fracture energy.